The STRATEGI KOMUNIKASI PEMASARAN GUNA MENINGKATKAN LOYALITAS KONSUMEN KEPESERTAAN PADA BPJS KETENAGAKERJAAN KOTA MAGELANG - An Nisa' Puspita Dewi; Hanung Eka Atmaja (Creative Research Management Journal, 2021)
The purpose of this study is to know labor and communication strategies in increasing theloyalty of wage workers. The results of this study indicate that employment BPJS is doingquite well with marketing communications, and that many loyal companies continue to usethe workforce's social security programs. The writer uses a descriptive method with thequalitative approach of describing, recording, analyzing and explaining the conditions thatare occurring within the company using the data-collection technique of interviews with thecompany's marketing division. The welfare of the worker is a temporal and spiritual meetingof needs both inside and outside work relationships that can improve worker performanceand productivity and thus create a healthy and comfortable working environment. One of theworker's welfare is protecting the worker. Indonesia has a special agency aimed at protectingworkers which is job BPJS. Bank Indonesia the central bank/bi decided to raise itsbenchmark interest rate by 25 basis points to 8.25 percent, he said. In promoting civilityBPJS and labor needs a good marketing communication startegi. Good marketing strategiescan increase customer loyalty to continue using products or programs from labor BPJS.